INNOVATIVE UPLC METHOD FOR CONCURRENT QUANTIFICATION AND PHARMACOKINETIC ANALYSIS OF NIRMATRELVIR AND RITONAVIR IN RAT PLASMA - RAJU, GOPE EDWARD; POTTENDLA, SRIKANTH; YAPARTHI, SUNEETHA (International Journal of Applied Pharmaceutics, 2025)
Objective: The primary goal of this study was to develop a rapid, robust, and sensitive UPLC method for the simultaneous estimation of Nirmatrelvir and Ritonavir in rat plasma using Lopinavir as an internal standard. This method aimed to improve upon existing approaches by offering faster run times, superior sensitivity, and thorough linearity, matrix effect, accuracy and precision, recovery and stability in accordance with USFDA guidelines. Methods: The UPLC analysis was carried out using a Waters Acquity UPLC system equipped with a PDA detector. An Acquity UPLC BEH Phenyl column (100 mm x 2.1 mm, 1.7 µm) was used for the separation process, with an isocratic mobile phase of buffer (Ammonium formate of pH-2.5 adjusted with 0.1% formic acid), flow rate 0.2 ml/min. Detection occurred at 236 nm, and the injection volume was 5 µl**. Results: Analysis was performed within 3 min, with a linear concentration range of 300-12000 ng/ml (r² = 0.99994±0.018) for Nirmatrelvir and 200-8000 ng/ml (r² = 0.99985±0.006) for Ritonavir. The extraction recovery results of Nirmatrelvir and Ritonavir were 97.17, 97.34, 97.34% and 96.80, 97.31, 96.95%, respectively and for matrix effect results were 97.18, 97.01 and 97.50, 97.58 at different QC concentration levels. Precision and recovery study results were determined within the acceptable limit. Conclusion: This UPLC method provides a substantial improvement in terms of speed, sensitivity, and robustness, making it well-suited for high-throughput pharmacokinetic studies of Nirmatrelvir and Ritonavir.